PENGEMBANGAN KONSEP DIRI TERHADAP ANAK SEKOLAH DASAR - Ridwan Prasetyo; Edy Soesanto; Abizard Haykal; Aji Dewa Abdulloh; Yossie Saputra (CV. Adiba Aisha Amira, 2024)
The purpose of this study is to determine the development of elementary school children's self-concept and what factors influence it. Self-concept becomes very important both in education and in life. Meeting the needs of an ever-changing environment will always require creative individuals and organizations. This research uses library research methodology. This research involves literature research. Literature-based research is a type of research in which literature is used as the object of research This research will discuss the role of parents, teachers, society, education, creativity in developing self-concept.